Abiotrophia Defectiva as a Rare Cause of Mitral Valve Infective Endocarditis With Mesenteric Arterial Branch Pseudoaneurysm, Splenic Infarction, and Renal Infarction: A Case Report - Li, Jiayu; Zhou, Li; Gong, Xuhe; Wang, Yuan; Yao, Daokuo; Li, Hongwei (Frontiers in Medicine, 2022)
Introduction: Abiotrophia defectiva (A. defectiva) is a rare species leading to infective endocarditis (IE) with poor prognosis. We describe a previously healthy patient with mitral valve infective endocarditis caused by A. defectiva. Case report: A young man was admitted with intermittent fever. Echocardiography confirmed a vegetation on mitral valve with evidence of valve perforation and severe mitral regurgitation. Three sets of blood cultures became positive for A. defectiva. As he presented with manifestations of mesenteric arterial branch pseudoaneurysm, splenic infarction and renal infarction, mitral valve replacement and embolization of superior mesenteric aneurysm were operated during eight weeks’ targeted antibiotic therapy. Conclusion: This case emphasizes the importance of considering A. defectiva as a rare but important cause of IE and of performing blood culture to make its accurate diagnosis and timely anti-infective treatment. Early surgical management and active prevention of complications have been associated with a favorable prognosis.